Systematic Literature Review: Peran Kualitas Pelayanan Fiskus dalam Meningkatkan Kepatuhan Wajib Pajak - Enjelica Netanya Budiansyah; Sri Wahyuning; Titik Rianawati; Galuh Aninditiyah; Henny Henny (CV. Denasya Smart Publisher, 2026)
This study aims to investigate the influence of tax sanctions and tax officer service quality on taxpayer compliance based on the results of six empirical investigations in Indonesia. A literature synthesis approach revealed that tax sanctions have a significant positive effect on restaurant taxpayers in Palembang, motor vehicle taxpayers in Makassar, and individual taxpayers in Sleman, but no significant effect on MSMEs in Padang due to weak policy socialization. The quality of tax officer service is the most constant factor, having considerable effect in four trials, although the effect is diminishing when the internal knowledge of taxpayers is already strong as in the case of Denpasar and Bandung. The effectiveness of sanctions and services is context dependent and varies by kind of taxpayer, the extent of socialization of the policy, and the primacy of internal factors such as moral consciousness. These findings suggest that tax policy measures should be segmented particularly and are not amenable to a one-size-fits-all strategy. Policies should be customized to the characteristics and local conditions of each taxpayer group in order to achieve optimal compliance outcomes.